Akidah Akhlak Teachers’ Role in Building Students’ Learning Responsibility: Peran Guru Akidah Akhlak dalam Membangun Tanggung Jawab Belajar Siswa - Hayati, Nilna Zahril; Nisak, Nur Maslikhatun (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Education serves as a foundation for character formation, and in Islamic schools, Akidah Akhlak teachers hold a strategic role in guiding students’ moral and academic development. Specific background: At the elementary level, fostering responsibility in learning is crucial, yet many students still struggle to demonstrate consistent discipline and accountability. Knowledge gap: Limited studies have comprehensively explored how Akidah Akhlak teachers practically shape students’ responsibility in daily learning contexts. Aims: This study aims to analyze the role, methods, and strategies of Akidah Akhlak teachers in cultivating learning responsibilities among grade IV students at SD Muhammadiyah 1 Waru Sidoarjo. Results: Using a qualitative descriptive approach through interviews, observations, and documentation, the findings show that teachers employed modeling, group discussions, independent tasks, and exemplary conduct, which effectively nurtured students’ responsibility in completing assignments, engaging actively in class, and adhering to school rules. Novelty: The study demonstrates that the integration of moral values in Akidah Akhlak instruction creates a sustainable character-building framework within elementary education. Implications: These findings emphasize the importance of teacher strategies in religious education to strengthen both academic responsibility and moral character for future societal contributions. Highlights: Akidah Akhlak teachers foster responsibility using diverse strategies. Moral values integration strengthens students’ learning discipline. Findings support character-based approaches in Islamic education. Keywords: Akidah Akhlak, Teacher’s Role, Learning Responsibility, Character Education, Elementary Students